Relações entre a professora de música e os alunos-presidiários: um estudo de caso etnográfico em Santa Maria-RS - Medeiros, Maria Augusta dos Santos (2009)
This work refers to the pedagogical-musical process as a total social fact on the music classes developed on the School/Center Julieta Ballestro located on the Regional Prison of Santa Maria RS/Brazil. Having as methodology the qualitative research and as method the study of ethnographic case, we can comprehend the study of the human beign from the musical perspective. Being a study of the totality, we find at the Prison six contexts: the juridical, where the institution Prison is presented to the society, since arising until arrives to the Regional Prison of Santa Maria; the institucional, that represents the School/Center Julieta Ballestro, since foundation and reason of the name, until the analysis of the Political Pedagogical School Project; the historical, where I tell how the project of music classes on the Prison began; the morphological, where the physical place and the sensations of entering in a Prison are described; the socio-cultural, envolving the prisioners routine until the society vision upon an inmate and finally the teaching and learning context, being this the research principal focus, envolving all the contexts described previously. The general objective of this dissertation is: to investigate the pedagogical-musical process (Kleber, 2006) as a total social fact (Mauss, 2003) on the music classes at the School/Center Julieta Ballestro. Having as specific objectives: to comprehend the penitentiary culture in relation to the pedagogical-musical process on the music classes; to relate the Prison daily life with the pedagogical-musical process on the music classes. The work is divided in six parts. The first presents the dissertation construction and its objectives. The second, refers to the contexts founded at the Prison to its realization. The third is where I present the pedagogical-musical process, as well as what is a total social fact and the link of the pedagogical-musical process as a total social fact under the perspectives of Libâneo (2000). The fourth, presents the methodology, the perspectives of the qualitative research, of the sutdy of ethnographic case and the tools used for data gathering: questionnaire for the inmates-students selection; semi-structured interviews; the audio records as product of the music classes and of the analyzed documents. The fifth refers to the analysis of the gathered data to comprehend and reach the objectives of this research. On the data analysis, we could listen the inmates voice to comprehend the pedagogic-musical process that occurs on the music classes, being able to observe that cop of the routine , learn something, it s done! , are lines that make the interlacing of the contexts part of the classes. Now, the last part of this dissertation, refers to the final considerations, where the relevance of this study with prisioners on the areas of Education and Musical Education, is made by the fact of demystifying the place prison and show that a study with scholar or non-scholar comunities is possible, because the richness of cultural information that each of these places show us can contribute to a work closer to the human being.